2012
DOI: 10.1111/j.1365-2125.2011.04118.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin inhibitors acutely improve insulin sensitivity without affecting insulin secretion in healthy human volunteers

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• New onset diabetes after transplantation is related to treatment with immunosuppressive medications. Clinical studies have shown that risk of new onset diabetes is greater with tacrolimus compared with ciclosporin. The diabetogenicity of ciclosporin and tacrolimus has been attributed to both beta cell dysfunction and impaired insulin sensitivity. WHAT THIS STUDY ADDS• This is the first trial to investigate beta cell function and insulin sensitivity using gold standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 51 publications
(60 reference statements)
3
29
0
Order By: Relevance
“…On the other hand, new-onset diabetes after transplantation related to treatment with immunosuppressive medications is an important complication. In fact, the acute effects of intravenous calcineurin inhibitors (CsA) and TAC infusions in healthy volunteers include increased IS [22]. However, chronic use of TAC impairs insulin secretion at multiple distal sites in stimulus-secretion coupling [23].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, new-onset diabetes after transplantation related to treatment with immunosuppressive medications is an important complication. In fact, the acute effects of intravenous calcineurin inhibitors (CsA) and TAC infusions in healthy volunteers include increased IS [22]. However, chronic use of TAC impairs insulin secretion at multiple distal sites in stimulus-secretion coupling [23].…”
Section: Discussionmentioning
confidence: 99%
“…In 10 healthy human volunteers with normal BMI (24.7 Ϯ 0.5 kg/m 2 ), Øzbay et al (69) showed that an acute infusion of CNIs over 5 hours increased insulin sensitivity as determined by hyperinsulinemic-euglycemic clamp. A greater increase in sensitivity was observed with cyclosporine (25%) than tacrolimus (13%), but there was no change in first-phase insulin secretion or insulin pulsatility.…”
Section: Role Of Immunosuppression Agentsmentioning
confidence: 99%
“…Corticosteroids, for example, induce insulin resistance in a dose-dependent manner by decreased beta-cell insulin production, increased gluconeogenesis, and decreased peripheral glucose utilization [38]. Calcineurin inhibitors inhibit insulin synthesis and secretion by pancreatic beta-cells [39]. mTOR inhibitors block B-cell proliferation, theoretically increasing the risk for diabetes, but also increases GLUT-4 signaling in insulin-responsive cells [40].…”
Section: Diabetesmentioning
confidence: 99%